Research Trends in Laboratory Safety within Science Education: A Bibliometric Analysis (2016–2025) - Nur Lathifah Putri Ramadani; Roudhoutul Aulia Rochim; Noer Af’idah; Himatul Aliyah (Alpatih Harapan Semesta, 2026)
This study aims to analyze research trends on laboratory safety in science education using a bibliometric approach. Although laboratory safety has become increasingly important in educational settings, comprehensive bibliometric studies focusing specifically on science education remain limited. Data were retrieved from the Scopus database covering the period 2016–2025, resulting in 1,089 documents analyzed using Biblioshiny. Several bibliometric indicators were employed, including publication trends, co-authorship analysis, country and affiliation productivity, keyword co-occurrence networks, and thematic mapping. The findings indicate a steady growth in publications, reflecting increasing global interest in laboratory safety within educational contexts. The analysis reveals that research is dominated by a few leading countries, particularly the United States and China, while authorship patterns show strong collaboration but no single dominant contributor. Furthermore, keyword and thematic analyses demonstrate that the field is primarily driven by human-centered and empirical studies, with emerging trends toward technology-based approaches such as machine learning. However, pedagogical aspects, including laboratory instruction and hands-on learning, remain less integrated within the core research structure. These findings provide important implications for future research, science education policy, and curriculum development, particularly in strengthening the integration of laboratory safety practices within science teaching and learning.